Outbreak of Shiga toxin-producing Escherichia-coli-associated hemolytic uremic syndrome in Istanbul in 2015: outcome and experience with eculizumab - GÖKCE, İBRAHİM (SPRINGER, 2018)
BackgroundThis study aims to identify epidemiological and clinical characteristics of patients and report our experience with eculizumab treatment during an outbreak of hemolytic uremic syndrome (HUS) caused by Shiga toxin-producing Escherichia coli (STEC) in Istanbul in 2015.MethodsThirty-two children (21 females, median age 3.25years) were included in this study. Demographic, clinical and laboratory data, and treatment details were retrospectively collected. Renal outcomes were assessed at last follow-up visit. To assess the effect of eculizumab on prognosis of STEC-HUS, subgroup analysis was performed on patients who required dialysis.ResultsA high number of cases occurred within a certain region of Istanbul. Stool samples were cultured from 21 patients (65%), and enteroaggregative E. coli (EAEC; n=7) and enterohemorrhagic E. coli (EHEC; n=3) strains were detected. Rates of dialysis treatment, neurological manifestations, and death were 59%, 25%, and 3%, respectively. Mean follow-up duration was 8.62.6months (range 3-12months). None of the patients (n=25) was on dialysis at the final visit. The complete renal recovery rate was 54%. Nine patients were treated with eculizumab. At final follow-up visit, no differences in estimated glomerular filtration rate, proteinuria level, or hypertension incidence were observed between patients treated with eculizumab and those not treated with eculizumab.Conclusions p id=Par4 An outbreak of EAEC occurred in a specific region of Istanbul. Livestock markets were suspected as the source. Evidence for beneficial effects of eculizumab on renal outcome was not clear in this cohort.
Keywords: Hemolytic uremic syndrome; HUS; Shiga toxin; STEC; Children; Eculizumab; CLINICAL-COURSE; COMPLEMENT; INFECTION; ACTIVATION; GERMANY